Association between Severity of Dyspepsia and Urea Breath Test Results in Patients with Positive Helicobacter pylori Serology - Catarina Budyono; Haris Widita; Ari fahrial Syam (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2018)
Background: Active Helicobacter pylori infection is considered to cause more severe dyspepsia symptoms compared to inactive infection. This study was aimed to determine the association between severity of dyspepsia and urea breath test (UBT) results in subjects with positive H. pylori serology.Method: This study was a cross-sectional study in 60 subjects with positive H. pylori serology in Provincial General Hospital of West Nusa Tenggara. Severity of dyspepsia was measured using modified Glasgow Dyspepsia Severity Score (GDSS) questionnaire. Diagnosis of active H. pylori infection was made using 14C UBT examination.Results: Proportion of active H. pylori infection in subjects with positive serology was 20%. The average of modified GDSS score in all patients was 1.95 (SD + 1.78), with minimal score of 0 and maximal score of 7. There was a statistically significant difference between average of modified GDSS score and positive and negative UBT results, (p = 0.027). The cut-off point value of modified GDSS to diagnose positive UBT was 3.8. Results of diagnostic test with modified GDSS as a test and UBT results as the gold standard indicated sensitivity of 41.6% and specificity of 85.4%. Conclusion: There was a significant difference between modified GDSS score in patients and positive and negative H. pylori infection. In areas which did not have UBT examination, eradication in patients with positive serology and GDSS score of more than or equal to 4 could be considered.